2000
DOI: 10.1046/j.1365-2567.2000.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐independent inhibition of dendritic cell maturation by aspirin

Abstract: SUMMARYWhen immature human myeloid dendritic cells were differentiated in vitro in the presence of aspirin, they were unable to stimulate T-cell proliferation. Aspirin and its major metabolite salicylate changed the surface marker phenotype of dendritic cells. The drugs particularly suppressed the levels of CD83 and the secreted p40 unit of interleukin-12 (IL-12), both markers of mature dendritic cells; 50% inhibitory concentration (IC 50 ) values were 2 . 5 mM, a concentration more than 100 times greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
51
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 43 publications
8
51
0
Order By: Relevance
“…It has been reported that aspirin inhibits bioactive IL-12 production by macrophages (17) and IL-12p40 secretion by monocyte-derived DC (28). Our results confirm the inhibitory effect of aspirin on IL-12p40 expression.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…It has been reported that aspirin inhibits bioactive IL-12 production by macrophages (17) and IL-12p40 secretion by monocyte-derived DC (28). Our results confirm the inhibitory effect of aspirin on IL-12p40 expression.…”
Section: Figuresupporting
confidence: 90%
“…It is also the first study in which DC exposed to aspirin have been tested for homing ability and capacity to sensitize recipients for cell-mediated immune responses. While we were completing this report, Matasic et al (28) observed that aspirin inhibited the maturation of human monocyte-derived DC. There are several differences between this latter study and the present report.…”
Section: Discussionmentioning
confidence: 66%
“…20 We measured p40 in the supernatants of the cells described in Figure 1 and found that the levels of this molecule closely followed the levels of CD83 with a 1-day lag ( Figure 2). The lag might reflect the differences in regulation of gene expression and/or in the post-translational processing inherent in secretion.…”
mentioning
confidence: 84%
“…LPS can also increase PLA 2 phosphorylation and AA release (31). To study the respective role of each isoform of COX in PGE 2 production and APC functions, we used drugs, such as indomethacin, a COX-1 preference inhibitor (32,33); SC-560, a COX-1-selective inhibitor (34); and NS-398, a COX-2-selective inhibitor (35,36).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%